Faszyzm w ujęciu Antoniego Derynga - Staszewski, Wojciech Szczepan (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
A heated discussion regarding Italian fascism and German national socialism is still ongoing. Views of columnists and politicians voiced in the period of creation of these ideologies are often studied in this context. On the other hand, the views of lawyers on the matter at hand are references considerably less, even though those presented by constitutionalists and experts in international law are often of considerable interest. This article was devoted to author and lawyer of undisputed renown, Professor Antoni Deryng, whose works significantly contributed to the study of international and constitutional law, and in particular to the emerging Italian fascism. The article offers a brief characterization of Antoni Deryng and his scholarly achievements as well as an analysis of the diagnosis of fascism that he presented in his work “Faszyzm a ustrój Włoch współczesnych” [Fascism and the political system contemporary Italy] published in 1937. The sources of this study include archival material obtained during study visits in the Archive of The John Paul II Catholic University of Lublin. This work also relies on scholarly texts, including those authored by Prof. Antoni Deryng. In this context, a historical and retrospective approach that takes into account the issues discussed in the contemporary perspective is applied.
Keywords: Deryng, Antoni (1901-1978); prawo międzynarodowe; prawo konstytucyjne; faszyzm; włoski system polityczny